Manajemen Kepala Sekolah dalam Implementasi Profil Pelajar Pancasila di Sekolah Dasar Islam Terpadu Bina Insani Kota Semarang - cayantoro, sigit; Murniati, Ngurah Ayu Nyoman; Abdullah, Ghufron (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
Research results 1) The principal's planning in implementing the Pancasila student profile at SD IT Bina Insani Semarang City includes 1) Developing the School Vision, Mission and School Goals; 2) Prepare RKJM, RKT, RKAS according to school needs; 3) Designing dimensions, themes and time allocation for the project to strengthen the profile of Pancasila students; 4) Create a project priority activity module. 2) The organization of school principals in implementing the Pancasila student profile at SD IT Bina Insani Semarang City is 1) Formation of management, 2) Division of work tasks according to their potential, 3) Standard SOPs for implementing tasks (job description) 4) Coordination and communication in all fields . 3) The principal's implementation of the Pancasila Student Profile at SD IT Bina Insani Semarang City includes instructing all teachers to 1) carry out classroom learning based on themes and projects; 2) carry out a project to strengthen the profile of Pancasila students in the independent dimension on a priority scale; 3) carry out a project to strengthen the profile of Pancasila students in the Gotong Royong dimension on a priority scale; 4) implementing a learning model with the 4C principles, namely critical thinking, communication, collaboration and creativity 4) Supervision of the school principal in implementing the Pancasila Student Profile at SD IT Bina Insani Semarang City, including internal supervision carried out by the principal and supervisor, then external supervision carried out by the school committee From a technical perspective, supervision is carried out using two approaches, namely direct technical supervision and indirect supervision in the form of reports.